Cytogenetic and biochemical aspects of the cellulolytic fungus Humicola sp. - Rodrigues, E. C. [UNESP]; Pizzirani-Kleiner, A. A.; Tanaka, Y.; Jorge, J. A. (Elsevier, 1991)
Twenty seven morphological mutants were isolated from a wild strain of Humicola using physical and chemical mutagens. Cytological observations of the nuclei of 250 spores of the wild strain indicated that the most frequent class contained 12 nuclei. This may permit the occurrence of heterokaryosis and account at least in part for the variability observed. The distribution of number of nuclei per spore in the morphological mutants showed maximum frequencies for classes of 3, 6, 12, 18 and 24 nuclei, with 3 possibly being the basic number of nuclei in the spores of this species. The interaction between several pairs of morphological mutants produced pigmented conidia similar to those of the wild strain, indicating the occurrence of either syntrophism or morphological complementation. Exoglucanase, endoglucanase, β-glucosidase, amylase and neutral protease activities were measured in the wild strain and in some morphological mutants. β-Glucosidase activity was higher in the mor13 mutant than in the wild strain and mor21 was found to be the best amylase producer. A highly significant correlation coefficient was detected between exoglucanase and endoglucanase activities, suggesting that these two activities may be co-regulated in this fungus. © 1991, British Mycological Society. All rights reserved.